2016
DOI: 10.17507/tpls.0608.03
|View full text |Cite
|
Sign up to set email alerts
|

A Critique of Politeness Theories

Abstract: Abstract-This paper presents a critique of politeness theories. As such, it aims to show the shortcomings and defects of the different theoretical foundations and pragmatic models of politeness. This work is hopefully supposed to be significant for the specialists and analysts in the field of pragmatics, discourse analysis, sociolinguistics and conversational analysis, ethnomethodology and communication studies. On the basis of the results of the criticism, it has been concluded that politeness theories suffer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…She views communication as an activity that is intrinsically risky and harmful (Ibid). Politeness is addressed here as referring to conversational interlocutors' tools to reduce the risk and the tension (Al-Hindawi & Alkhazaali, 2016). Referring to the language politeness theories above, using a bottle of sopi or tuak in speech is one of the politeness strategies used by speakers and interlocutors to create harmonious interactions during the belis negotiation process.…”
Section: Discussionmentioning
confidence: 99%
“…She views communication as an activity that is intrinsically risky and harmful (Ibid). Politeness is addressed here as referring to conversational interlocutors' tools to reduce the risk and the tension (Al-Hindawi & Alkhazaali, 2016). Referring to the language politeness theories above, using a bottle of sopi or tuak in speech is one of the politeness strategies used by speakers and interlocutors to create harmonious interactions during the belis negotiation process.…”
Section: Discussionmentioning
confidence: 99%
“…It seeks to establish links and relationships between people, community resources and service providers, as well as achieve justice and equality among different population groups, and encourage the exchange of information, experience, and resources among different institutional structures. It adopts a scientific and general perspective on human issues and seeks solutions to problems (Hindawi, 2015).…”
Section: Theory Of Professional Practicementioning
confidence: 99%
“…Other explorations of the politeness theory by a variety of authors have suggested several kinds of impacts related to the use of face threats (see Al-Hindawi and Alkhazaali, 2016 for a review). These authors indicate that most scholars who focus on politeness conceptualize it as a strategy aimed at achieving group harmony or comity while achieving pragmatic goals such as making a decision or promoting relationships.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%